Graphical Performance Measures for Practitioners to Triage Split Failure Trouble Calls. Issue 1 (January 2014) - Freije, Richard S.; Hainen, Alexander M.; Stevens, Amanda L.; Li, Howell; Smith, W. Benjamin; Summers, Hayley; Day, Christopher M.; Sturdevant, James R.; Bullock, Darcy M.
Detector occupancy is commonly used to measure traffic signal performance. Despite improvements in controller computational power, there have been few innovations in occupancy-based performance measures and little integration with other data. This paper introduces and demonstrates the use of graphical performance measures based on detector occupancy ratios to verify potential split failures and other signal timing shortcomings reported to practitioners by the public. The proposed performance measures combine detector occupancy during the green phase, detector occupancy during the first 5 s of the red phase, and phase termination cause (gap out or force-off). They are summarized by time of day to indicate whether the phase is undersaturated, nearly saturated, or oversaturated. The graphical performance measures and related quantitative summaries provide a first-level screening and triaging tool to help practitioners assess user concerns about whether sufficient green times are being provided to avoid split failures. They can also provide outcome-based feedback to staff after split adjustments have been made to determine whether operation improved or worsened. The paper demonstrates how the information was used to make an operational decision to reallocate green time that reduced the number of oversaturated splits on minor movements from 304 to 222 during a Thursday 0900 to 1500 timing plan and from 240 to 180 during a Friday 0900 to 1500 timing plan.